NILAI-NILAI BUDAYA KISAH CERITA RAKYAT KERINCI : STUDI STRUKTURAL DAN SEMIOTIK - Nazurty, Nazurty (Pena : Jurnal Pendidikan Bahasa dan Sastra, 2015)
Tale is a means of a singing folklore. This research is trying to explore the cultural values of the tale performed in Kerinci’s local tradition to see the hajj participants off. This research applies a qualitative study in the form of content analysis with structural and semiotic approach. Structural approach is aimed at revealing cultural values related to structural elements of tale, and semiotic approach is used to find out the meaning of both cultural value and cultural semiotic signs as such icon, index, and symbol. The findings on the structural elements of Kerinci’s tale can be classified into: first, the tale of conventional poetry where the structure refers to the existing conventions. Second, the themes are in the forms of a separation, grief and compassion, advice, guidance, and love desire, desire, hope, or ideals. The findings on cultural value is human relationships with God are obedience, resignation, providence of God, the power of God, gratitude, the power of faith. Keywords : Tale structures, moral values, semiotic symbols.